Influence of Nozzle Design on the Performance of a Partial Combustion Lance: A CFD Study - Law, Woon Phui; Jolius, Gimbun (Elsevier, 2015)
This paper presents a computational fluid dynamics (CFD) simulation of a partial combustion lance (PCL) aiming to evaluate the effect of nozzle design on its performance. Four turbulence models, namely, standard k-ε (SKE), realisable k-ε (RKE), renormalised (RNG) k-ε and Reynolds stress model (RSM) were used. The combustion process was modelled using the species transport model, whereas the heat transfer was calculated by considering a combined convection-radiation boundary condition. The best CFD prediction was obtained using the second-order discretisation, standard pressure, unsteady solver and RSM with a 6% deviation from the experimental data. The modified nozzle design shows increases in excess of 45% of the peak combustion temperature in the PCL. The findings from this work may be useful for design retrofits of a PCL.